The Dispute around Same-Sex Marriage in Costa Rica: Arguments and Actions of Conservative Religious Activism (2017–2021) - León-Carvajal, Arantxa (Religions, 2023)
This article examines the role assumed by Costa Rican conservative religious activism during the public controversy that arose in the Central American country regarding the legalization of same-sex marriage. This public debate found its highest point during the presidential elections of 2018. The article is divided into two parts. Firstly, it identifies the arguments used by conservative actors during the controversy, with special emphasis on the conceptions of democracy and human rights that informed their political praxis. Secondly, it ponders the significance that the politicization of religion in a conservative direction has had on the dynamics and democratic institutions of contemporary Costa Rica.